Lipid Peroxidation-Mediated Inflammation Promotes Cell Apoptosis through Activation of NF-κB Pathway in Rheumatoid Arthritis Synovial Cells - Geng Yin; Ying Wang; Xiao-min Cen; Min Yang; Yan Liang; Qi-bing Xie (Hindawi Limited, 2015)
Rheumatoid arthritis (RA) is a systemic autoimmune disease characterized by chronic inflammation of multiple joints. The central pathogenesis of RA is the proliferation of synovial fibroblasts in response to inflammatory cytokines. However, some of the targeted therapies for inflammation reactions do not display significant clinical improvement after initiation of therapy. Thus, the relationship between inflammatory responses and RA therapy is still incompletely understood. In the present study, we proposed to determine whether enhanced inflammations may lead to cell apoptosis in rheumatoid arthritis synoviocytes. Our results indicated that products of lipid peroxidations, 4-HNE, may induce synovial intrinsic inflammations by activating NF-κB pathways and it may lead to cell apoptosis. Pharmacological inhibition of NF-κB activation may reduce the 4-HNE mediated inflammation responses and subsequent cell apoptosis. Our results may help to clarify the role of inflammations on RA development and imply that blocking NF-κB activation may be partly beneficial for human RA therapy. These findings might provide a mechanism-based rationale for developing new strategy to RA clinical therapy.